(untitled) (Research, Society and Development, 2021)
Self-esteem is associated with quality of life, as it is seen as an important mental health indicator, and it is conceptualized as a set of feelings and thoughts of the individual about his own value, competence and adequacy, which has a positive or negative attitude. negative towards you. Therefore, it is interesting to evaluate it because it is a sample of adolescents, as adolescence is a period of great physical, psychological and social changes. The objective of the work in question is to assess the self-esteem of adolescent students. The sample consisted of 36 students from two public schools in the municipality of Nazaré da Mata. We used as a method to apply the Rosenberg’s Self-Esteem Assessment Scale (1979) adapted to Portuguese by Hutz (2011) and a data collection form in order to characterize the investigated groups. For data analysis, we used the SPSS 20.0 program, and for descriptive analysis, the mean and standard deviation of the groups were observed. To analyze whether there were statistically significant differences between the groups, we used the t test for independent samples. The result showed that there were no statistically significant differences between the groups, despite the average of the full-time school being higher than the group of the part-time school.